2022
DOI: 10.1371/journal.pone.0261897
|View full text |Cite
|
Sign up to set email alerts
|

Blindness and visual impairment in Central Europe

Abstract: Purpose To assess the prevalence and causes of visual impairment and blindness in a Central European country. The findings may have implications for the planning of further research and development of therapies in order to prevent blindness. Setting Department of Ophthalmology, Medical University of Graz, Austria. Design Retrospective, epidemiological study. Methods The database of the Main Confederation of Austrian Social Insurances was searched for patients with visual impairment, legal blindness or de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 37 publications
0
8
0
2
Order By: Relevance
“…Other lesser important causes of blindness included posterior segment disorders and glaucoma. These two latter causes assume greater significance in the more industrialized nations, as reported by a blindness study from Central Europe [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other lesser important causes of blindness included posterior segment disorders and glaucoma. These two latter causes assume greater significance in the more industrialized nations, as reported by a blindness study from Central Europe [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…The definitions of blindness have evolved over the years internationally and in India [ 2 ]. A contemporary blindness study from Central Europe defined blindness as visual acuity ≤ 1/60 without visual field defects, as visual acuity ≤ 2/60 with quadrantanopsia, as visual acuity ≤ 4/60 with hemianopsia, or as visual acuity 6/60 with tunnel vision [ 3 ]. Similarly, it defined visual impairment as visual acuity ≤ 3/60 without visual field defects, as visual acuity 6/60 with quadrantanopsia, as visual acuity 6/20 with hemianopsia, or as visual acuity ≤ 6/6 with tunnel vision.…”
Section: Introductionmentioning
confidence: 99%
“…Their findings showed that among the working-age adults and children in Austria, inherited retinal and choroidal diseases were the leading causes of visual impairment and blindness, drawing attention to further research in emerging treatments for those diseases. 32 …”
Section: Discussionmentioning
confidence: 99%
“…Két évtized alatt is jelentősen változtak a gyengénlátáshoz vezető kórokok [5][6][7][8][9][10][11] (1. táblázat). Az 1980-as évektől folyamatos emelkedést mutat a mentális károsodással vagy genetikai betegséggel társult gyengénlátás.…”
Section: Táblázatunclassified